Proposing a Method of Organizational Diagnosis: Study Case - Andrei Valentin BAICU; George CARUTASU (Communications of International Proceedings, 2021)
The current dynamics of economic and technological phenomena, globalization and pandemic, have created difficulties in the permanent readjustment of organizations to events that follow one another quickly and change paradigms. Verification of the companies ’effectiveness requires the use of models or diagnostic frameworks that provide important information about the organization. Each of these models offers a different perspective, so for a clearer picture of the organization, the use of more organizational models and tools becomes welcome. This paper proposes a model of organizational analysis - the cyclical model of determinations - and presents a case study. The methodology used was non-intrusive, by interview, using a predetermined list of questions which are integral part of the proposed tool. This model offers an additional perspective in the analysis of an organization, anticipating in the same time the possible imbalances that may appear within it.
Keywords: Organizational Diagnosis; Organizational Diagnosis Model; Organizational Change Management Tools.